Impacts of the COVID-19 pandemic and the CARES act on earnings and inequality - Guido Matias Cortes; Eliza Forsythe (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2021)
Using data from the Current Population Surveys, we investigate the aggregate and distributional consequences of the Covid-19 pandemic and the associated public policy response on labor earnings and unemployment benefits in the United States up until February 2021. We find that year-on-year changes in labor earnings for employed individuals were not atypical during the pandemic months, regardless of their initial position in the earnings distribution. The incidence of job loss, however, was, and continues to be, substantially higher among low earners, leading to a dramatic increase in labor income inequality among the set of individuals who were employed prior to the onset of the pandemic. By providing very high replacement rates for individuals displaced from low-paying jobs, the initial public policy response was successful in reversing the regressive nature of the pandemic's impacts. We estimate, however, that recipiency rates for displaced low earners were relatively low. Moreover, from September onwards, when policy changes led to a decline in benefit levels, earnings changes became much more regressive, even after factoring in benefits.
Keywords: 330; Coronavirus; Beschäftigungseffekt; Einkommensverteilung; Arbeitsmarktpolitik; Wirkungsanalyse; USA